1996
DOI: 10.1007/bf00207353
|View full text |Cite
|
Sign up to set email alerts
|

TNRNFLRFamide and SDRNFLRFamide modulate muscles of the stomatogastric system of the crab Cancer borealis

Abstract: The effects of the extended FLRFamide-like peptides, TNRNFLRFamide and SDRNFLRFamide, were studied on the stomach musculature of the crab Cancer borealis. Peptide-induced modulation of nerve-evoked contractions was used to screen muscles. All but 2 of the 17 muscles tested were modulated by the peptides. In several muscles of the pyloric region, peptides induced long-lasting myogenic activity. In other muscles, the peptides increased the amplitude of nerve-evoked contractions, excitatory junctional potentials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…FMRFamides enhance transmitter release at crustacean neuromuscular junctions (Kravitz et al, 1980;Mercier et al, 1990;Skerrett et al, 1995;Worden et al, 1995;Jorge-Rivera and Marder, 1996;Friedrich et al, 1998). Our finding that one of the FMRFamides, DF 2 , is effective in modulating release in the fast but not in the slow neuron innervating the same muscle, is new, and makes generalized statements on the role of modulators precarious.…”
Section: Peptidergic Modulation Of Transmitter Release Is Axon Type-smentioning
confidence: 81%
See 1 more Smart Citation
“…FMRFamides enhance transmitter release at crustacean neuromuscular junctions (Kravitz et al, 1980;Mercier et al, 1990;Skerrett et al, 1995;Worden et al, 1995;Jorge-Rivera and Marder, 1996;Friedrich et al, 1998). Our finding that one of the FMRFamides, DF 2 , is effective in modulating release in the fast but not in the slow neuron innervating the same muscle, is new, and makes generalized statements on the role of modulators precarious.…”
Section: Peptidergic Modulation Of Transmitter Release Is Axon Type-smentioning
confidence: 81%
“…The effect of Ni 2ϩ was largely reversible after 20 min of washing with saline. 15.0 Ϯ 6.4 (n ϭ 8) (n ϭ 7) (n ϭ 6) (n ϭ 8) (n ϭ 11) (n ϭ 5) I (nA) (%) 73.5 Ϯ 4.9 2.3 Ϯ 1.5 35.0 Ϯ 3.9 77.8 Ϯ 6.1 20.6 Ϯ 4.4 13.0 Ϯ 3.8 (n ϭ 10) (n ϭ 7) (n ϭ 6) (n ϭ 11) (n ϭ 10) (n ϭ 6) The modulation of transmitter release by the peptide DF 2 involves -conotoxin-sensitive Ca 2؉ channels As many as 12 LRFamide-like peptides have been identified in crustaceans (Weimann et al, 1993;Sithigorngul et al, 1998Sithigorngul et al, , 2001Mercier et al, 2001), of which four have been shown to modulate transmitter release from neuromuscular endings in crayfish and lobster (Kravitz et al, 1980;Mercier et al, 1990;Skerrett et al, 1995;Worden et al, 1995;Jorge-Rivera and Marder, 1996;Friedrich et al, 1998). Among them is DRNFLRFamide, also referred to as DF 2 , which enhances junction potential amplitudes by increasing the number of transmitter quanta released (Skerrett et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…In that study, the ACO was also studied extensively for the presence of co-transmitters but none were identified. One function of circulating hormones, including CabTRP Ia, is to modulate the properties of muscles that mediate movements of the foregut (Jorge-Rivera and Marder, 1996;Messinger et al, 2005). Therefore, POC-mediated release of CabTRP Ia may well coordinately trigger the gastric mill rhythm and modulate the response of gastric mill muscles to the incoming motor pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Further, from presynaptic transmitter release to the regulation of contraction machinery, all aspects of the neuromuscular transform are subject to neuromodulation and thus can differ according to the behavioral state of the organism (Brezina, 2010;Brezina et al, 2000;Hooper and Weaver, 2000;Williams et al, 2013;Worden, 1998). Given the prevalence of neuromodulators acting on muscles, including in the STNS (Brezina, 2010;Fort et al, 2004;Hooper et al, 1999;Jorge-Rivera and Marder, 1996;Jorge-Rivera et al, 1998;Wali, 1985;Weimann et al, 1997;Worden, 1998;Wu and Cooper, 2012), it is possible that there are modulatory conditions in which the balance of depression and facilitation, and the properties of augmentation between the three muscles may converge. Similarly, relaxation kinetics are modulated, and the differences in summation between the three muscles could converge under a particular modulatory environment (Jing et al, 2010;Jorge-Rivera et al, 1998).…”
Section: Physiological Activity Rangementioning
confidence: 99%